PREVENTATIVE EFFECTS OF PROBIOTIC (MIACLOST) ON EXPERIMENTALLY INDUCED HYPOCALCEMIC RICKETS IN BROILER CHICKS. - Ameen, N. A.; Abdul Rahman, N. R.; Hassan, A H (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A trial was conducted to study the effects of probiotic (Miaclost) supplement on experimentally induced hypocalcemic rickets in broiler chicks, a total of 180 one-day-old broiler chicks (Ross 308) were randomly divided into three equal groups 60 chicks per group with 3 replicates (20 birds /replicate) the dietary treatments consisted of a normal ration for G1, calcium-deficient ration 5% for G2 and calcium-deficient ration with addition of probiotics in drinking water for G3.Initial signs of rickets have been observed at 35-day of age in G2.while, in G1 and G3 no clinical signs observed, the gross lesions appeared enlargement of parathyroid gland, costochondral junction and increase in the width of growth plate of tibial bone of G2 whereas no gross lesions recorded in G1 and G3, the histopathological examination of parathyroid gland in G2 there were a focal parathyroid hyperplasia and increasing in numbers of syncytial cells and normal in G1 and G3, no intestinal histopathological changes in G1 and G2 and increase in height and width of the intestinal villi  in probiotic group G3. Marked increase in the thickness of proliferation zone within growth plate of tibia bone in G2 and normal thickness in G1 and G3. the serum biochemical analysis of calcium of G2 recorded significantly low level in G2 and high level in G3  comparatively with G1, finally the serum alkaline phosphatase values were high significantly in G2 and normal in G3, it is concluded that probiotic (MiaClost) can be used as prophylaxis to prevent hypocalcemic rickets in broiler chicks